Pemberdayaan Masyarakat pada Kelompok Belajar PKBM dalam Pembuatan Lulur Tradisional Berbahan Baku Kayu Bangkal untuk Kesehatan Kulit - Chandra Chandra; Eddy Rahman; Meilya Farika Indah; Norsita Agustina; Deni Suryanto (Jurnal Abdimas Kesehatan (JAK), 2026)
As we age, the skin will undergo an aging process. Aging is caused by sharing factors both from inside and outside the body. The benefits of scrubbing ingredients from kuyu bangkal can soften and smooth the texture of the skin, making it more supple and soft to the touch. This scrub is believed to be able to remove dirt, excess oil, and dead skin cells from the skin, thus making the skin feel fresher and cleaner. Bangkal wood is a material that is often found in the community, the use of bangkal wood scrub for beauty is still very minimal known to the public. Bangkal scrubs are the basic ingredient in the tradition of the balulur of the Banjar tribe community which is currently decreasing. The purpose of this study is to describe the processing and application of bangkal scrubs in the Banjar tribal balulur tradition. The target of this activity is the Al Azhar PKBM study group in Banjarmasin City. The method is by providing training/demonstration in making scrubs made from bangkal wood. The results of community service activities are enthusiastic partners in the implementation of these activities and this activity is carried out pre and post test with the results obtained by pretest of 60% and post test of 95% so that they can find out how to make bangkal wood scrubs where the raw materials are products of local wisdom in the local area and partners get skills to make bangkal wood scrubs. The conclusion in this activity is that partners have gained increased knowledge about the benefits of bangkal wood for scrubs